2017
DOI: 10.3389/fneur.2017.00065
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in Multiple Sclerosis: The Role of Aversion to Ambiguity for Therapeutic Inertia among Neurologists (DIScUTIR MS)

Abstract: ObjectivesLimited information is available on physician-related factors influencing therapeutic inertia (TI) in multiple sclerosis (MS). Our aim was to evaluate whether physicians’ risk preferences are associated with TI in MS care, by applying concepts from behavioral economics.DesignIn this cross-sectional study, participants answered questions regarding the management of 20 MS case scenarios, completed 3 surveys, and 4 experimental paradigms based on behavioral economics. Surveys and experiments included st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 44 publications
2
90
0
Order By: Relevance
“…Despite significant therapeutic advances, many patients remain undertreated, especially those with chronic medical conditions, such as atrial fibrillation, hypertension, and multiple sclerosis (MS) ( 1 4 ). One of the explanations relates to knowledge integration and knowledge-to-action gaps in therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite significant therapeutic advances, many patients remain undertreated, especially those with chronic medical conditions, such as atrial fibrillation, hypertension, and multiple sclerosis (MS) ( 1 4 ). One of the explanations relates to knowledge integration and knowledge-to-action gaps in therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is known that physicians can be aware and informed about the current management of the common medical conditions they see in their daily clinical practice, but fail to integrate available information (e.g., severity of the condition, risk of progression, imaging findings, demographic factors affecting outcomes) and to implement best practice recommendations based on the available knowledge. This phenomenon may lead to therapeutic inertia (TI) usually associated with poorer outcomes ( 2 4 ). TI is a term that defines the absence of treatment initiation or intensification in patients when treatment goals are unmet.…”
Section: Introductionmentioning
confidence: 99%
“…Aversion to ambiguity in the financial domain was the most relevant predictor of TI (OR 7.39; 95% CI 1.40-38.9), followed by low tolerance to uncertainty (OR 3.47; 95% CI 1.18-10.2). 5 This finding was replicated among neurologists from Argentina and Chile (n = 115; OR for aversion to ambiguity: 2.91; 95% CI 1.06-8.04; OR for low tolerance to uncertainty: 1.47; 95% CI 1.02-2.11). Similar associations were found for stroke prevention in the management of atrial fibrillation (most common cardiac arrhythmia) among cardiologists and general practitioners.…”
Section: Application To Medical Decision-makingmentioning
confidence: 73%
“…7 Our group studied therapeutic decisions in multiple sclerosis (MS) made by neurologists applying experiments evaluating risk, ambiguity, and herding. 5 There are many treatments available for MS, ranging from low efficacy and low risk of side effects to highly efficacious agents with greater risk of severe side effects. We found that 7 out of 10 neurologists from Spain (n = 96) failed to escalate treatment when recommended by guidelines, a phenomenon called therapeutic inertia (TI).…”
Section: Application To Medical Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation